Voltammetric Determination of Ivabradine Hydrochloride Using Multiwalled Carbon Nanotubes Modified Electrode in Presence of Sodium Dodecyl Sulfate - Ali Kamal Attia; Nisreen Farouk Abo-Talib; Marwa Hosny Tammam (Tabriz University of Medical Sciences, 2017)
Purpose: A new sensitive sensor was fabricated for the determination of ivabradine hydrochloride (IH) based on modification with multiwalled carbon nanotubes using sodium dodecyl sulfate as micellar medium to increase the sensitivity. Methods: The electrochemical behavior of IH was studied in Britton-Robinson buffer (pH: 2.0-11.0) using cyclic and differential pulse voltammetry. Results: The voltammetric response was linear over the range of 3.984 x 10-6-3.475 x 10-5 mol L-1. The limits of detection and quantification were found to be 5.160 x 10-7 and 1.720 x 10-6 mol L-1, respectively. Conclusion: This method is suitable for determination of IH in tablets and plasma.